Generalized fermi derivative on the hypersurfaces - Ayşenur Uçar; Fatma Karakuş (MANAS: Journal of Engineering)
In this paper, generalized Fermi derivative, generalized Fermi parallelism, and generalized non-rotating frame concepts are given along any curve on any hypersurface in Eⁿ⁺¹ Euclidean space. The generalized Fermi derivative of a vector field and being generalized non-rotating conditions are analyzed along the curve on the surface in Euclidean 3-space. Then a correlation is found between generalized Fermi derivative, Fermi derivative, and Levi-Civita derivative in E³. Then we examine generalized Fermi parallel vector fields and conditions of being generalized non-rotating frame with the tensor field in E⁴. Generalizations have been made in Eⁿ.